Cinematic places - Baxter, Sarah (White Lion Publishing, 2023)
"Go beyond the big screen and explore the real places that inspired some of the greatest films of all time - brought to life through comprehensively researched text and stunning hand-drawn artwork. Travel journalist Sarah Baxter reveals 25 essential cinematic destinations around the globe, spanning different decades, directors and movie genres. Full-page colour illustrations instantly transport you to each location. You'll find that these places are not just backdrops to the tales told, but characters in their own right"--Publisher's description
Keywords: Motion picture locations; Travel in art; Travel / Guidebooks; Guidebooks